SOCIAL INTERACTION EXPERIENCES OF BEGINNING UNIVERSITY TEACHERS IN BUILDING OCCUPATION-RELEVANT COMPETENCIES - Anužienė, Birutė; Šatienė, Salomėja (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The article presents findings of a qualitative study focused on analysis of social interaction experiences of beginning teachers in higher education, whereby social interaction is construed as a dialogue, conversation, socio-cognitive conflict, and intersubjective solutions thereof, which influence the process of formation of new competencies.The aim of research is to show the prevailing experiences of beginning university teachers in building competencies within the context of social interaction - socio-cognitive conflict - situations. The research is based on the interactional ethnography approach. The research participants were newly hired teachers of different universities in Lithuania. The research shows that the degree of asymmetry in social relations is subject to differences in the status, experience, competencies, or age of the agents. In the context of intensity of socio-cognitive interaction, where it involves a small number or single-direction exchanges of views and opinions, socio-cognitive conflict will not necessarily be progressive in building new competencies. As regards the features of social and affective interaction, the situation of convenience - confrontation is the most favorable for the acquisition and formation of cognitive structures - competencies. Social and cognitive abilities of participants in a socio-cognitive conflict, as prerequisites for cognition, are essential for the acquisition of new structures - competencies.